Black Art: An Aesthetic Transformation for Freedom and Justice - Dhakal, Lekha Nath (KMC Research Journal, 2019)
This paper attempts to explore African Americans’ world view and its roots in Black Aesthetics. It also reveals that Black art is an aesthetic transformation of African Americans for freedom and an expectation of a higher level of life. Supporters of Black Aesthetics appealed to black artists to establish a new standard of judgment and beauty based on African myths, spirituality, belief systems and music in opposition to Western aesthetic. However, the Black Aesthetics had its origins in those first artistic resonances of black slaves in the form of spirituals, coded singing and signifying, and later in writings. Black aesthetic theory in the United States traces its origin to the literature of slavery and freedom. The slave narratives depict African-Americans’ artistic and academic labors to show their humanity and critical moments in the development of Black aesthetics. Writing about their own communities in order to establish a sense of self-worth and claiming their identities as African Americans are crucial elements in the works of many Black writers.